2005
DOI: 10.1007/s00439-004-1250-3
|View full text |Cite
|
Sign up to set email alerts
|

Variation in ITGB3 has sex-specific associations with plasma lipoprotein(a) and whole blood serotonin levels in a population-based sample

Abstract: A recent genome-scan identified the Leu33Pro polymorphism in the beta3 integrin (ITGB3) gene as a quantitative trait locus for whole blood serotonin level in a large Hutterite pedigree. Because both the Leu33Pro polymorphism and the serotonin system have been implicated in cardiovascular disease (CVD) risk and treatment response, we studied additional variation in ITGB3 and its relationship to intermediate phenotypes associated with CVD in the same population. We examined associations between 15 single nucleot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
25
2
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 48 publications
3
25
2
1
Order By: Relevance
“…Previous studies have found association between ITGB3 and whole blood 5-HT levels in males (Weiss et al, 2004(Weiss et al, , 2005a(Weiss et al, , 2005b, but our study is too small to support a sex-specific analysis. Additionally, allelic heterogeneity with regard to 5-HT levels is evident at ITGB3.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…Previous studies have found association between ITGB3 and whole blood 5-HT levels in males (Weiss et al, 2004(Weiss et al, , 2005a(Weiss et al, , 2005b, but our study is too small to support a sex-specific analysis. Additionally, allelic heterogeneity with regard to 5-HT levels is evident at ITGB3.…”
Section: Discussioncontrasting
confidence: 77%
“…Additionally, allelic heterogeneity with regard to 5-HT levels is evident at ITGB3. The amino-acid polymorphism that we genotyped in this study showed evidence for association with autism in previous studies, but did not show the strongest evidence for association with serotonin level in these studies (Weiss et al, 2005b(Weiss et al, , 2006. A haplotype of two TPH1 polymorphisms was associated with whole blood 5-HT by allele-wise ANOVA (p ¼ 0.046).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…19 Finally, several recently published studies have described significant SLC6A4 and ITGB3 interactions for both autism risk and 5-HT blood levels, with a male-specific effect. 10,[14][15][16][17]20 Despite these positive findings, several inconsistencies complicate their interpretation, possibly because of clinical and genetic heterogeneity in ASD. In particular, different alleles seem to be associated with autism and/or serotoninemia in independent samples at the ITGB3 and SLC6A4 loci.…”
Section: Introductionmentioning
confidence: 99%
“…En los estudios se ha demostrado un importante carácter hereditario de los niveles de serotonina en plaquetas tanto en individuos sanos como en autistas (23)(24)(25), y los genes SLC6A4 y ITGB3 fueron identificados como loci que tienen efecto sobre los niveles de serotonina en plaquetas (26)(27)(28).…”
unclassified